Albania : Technical Assistance Report-Monetary and Financial Statistics and Financial Accounts Mission. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance report on Albania focuses on: compiling and disseminating flow-based monetary and financial statistics (MFS) for the central bank, other depository corporations (ODCs), and other financial corporations (OFCs); compiling and disseminating quarterly financial accounts by institutional sectors; and developing a from-whom/to-whom matrix for financial instruments. The mission reviewed the quality of Albania's flow-based MFS, sectoral financial accounts and balance sheets, and provided technical guidance to improve their quality. The Monetary Policy Committee has requested flow-based monetary statistics as an additional vehicle to understand money and credit developments in the Albanian economy. Similarly, financial accounts by sector and financial balance sheets are considered increasingly important for analysis of financial stability and other macroeconomic developments. The mission also recommended that the BOA begins compiling quarterly sectoral financial accounts and balance sheets by mid-2021 starting with data from the first quarter of 2017.